Ontology-based Retrieval of Scientific Data in LIFE - Kirsten, Toralf; Uciteli, Alexandr (Proc. Workshop on Data Management for Life Sciences, 2015)
LIFE is an epidemiological study determining thousands of Leipzig inhabitants with a wide spectrum of interviews, questionnaires, and medical investigations. The heterogeneous data are centrally integrated into a research database and are analyzed by specific analysis projects. To semantically describe the large set of data, we have developed an ontological framework. Applicants of analysis projects and other interested people can use the LIFE Investigation Ontology (LIO) as central part of the framework to get insights, which kind of data is collected in LIFE. Moreover, we use the framework to generate queries over the collected scientific data in order to retrieve data as requested by each analysis project. A query generator transforms the ontological specifications using LIO to database queries which are implemented as project-specific database views. Since the requested data is typically complex, a manual query specification would be very timeconsuming, error-prone, and is, therefore, unsuitable in this large project. We present the approach, overview LIO and show query formulation and transformation. Our approach runs in production mode for two years in LIFE.